Demographic Expansion and Contraction in a Neotropical Fish during the Late Pleistocene-Holocene - Costa, Carolina L. N. (2019)
Demographic changes during the late Pleistocene-Holocene left signatures in the DNA of contemporary populations. These signatures reveal demographic phenomena like the increase or decrease in effective population size. In this paper we searched for signatures of demographic change in the DNA of the Neotropical freshwater fish Poecilia vivipara . Also, we investigated whether demographic changes are correlated with palaeoclimatic events of the late Pleistocene-Holocene, in particular, if changes in effective population size are correlated with expansion and contraction of available habitats, induced by global ice-volume changes and sea-level fluctuations. We used Bayesian Skyline Plot (BSP) analysis with sequences from the mitochondrial gene cytochrome b to estimate the ancestral demography of the Neotropical freshwater fish P. vivipara . To test the assumptions of neutrality and absence of population structure we used Tajima’s D and Spatial Analysis of Molecular Variance (SAMOVA), respectively. Effective population size of P. vivipara remained stable until 75,000 years ago, increased by 10-fold reaching a maximum at approximately 25,000 years ago, then suddenly declined at the Pleistocene- Holocene boundary. Variation in effective population size in P. vivipara correlates with expansion and contraction of habitats induced by sea-level fluctuations, caused by the advance and retreat of ice sheets during the Last Glacial Maximum (LGM).